Efficacy and Safety of Intravascular Lithotripsy in the Treatment of Calcified Peripheral Artery Disease: : A Systematic Review and Meta-Analysis - Sajdeya, Omar (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.